THE CONCEPT OF TEACHER ADAB IN THE BOOK OF MINHAJJUL MUTA'ALLIM WORK OF IMAM AL-GHAZALI - Siti Jaroyatun Ni'mah; Abid Nurhuda; Muhammad Al Fajri (Jendela PLS: Jurnal Cendekiawan Ilmiah Pendidikan Luar Sekolah, 2023)
Family and parents are the first educators for someone in introducing various things that are useful for his life. Schools and teachers are often seen as second parents for students, in which there is interaction between the two parties, so unwanted friction often occurs. Many scholars' books discuss adab between teachers and students to minimize this friction. One of them is the book Minhajjul Muta'allim by Imam Al-Ghazali. So the purpose of this research is to describe the concept of teacher etiquette in the book. The method used is a literature study with data collection techniques using documentation, then analyzed, and systematic conclusions are drawn. The results showed that the concept of teacher etiquette in the book Minhajjul Muta'allim by Imam Al-Ghazali has good morals, is polite, ikhlas in conveying knowledge has a forgiving nature, knows the characteristics of each student and masters the material presented so that he will be used as a role model for their students.